Psychometric testing of the nurses professional values scale-revised on family and community health nurses - Gasperini, Giulia (Nursing ethics, 2024)
BackgroundFamily and Community Health Nurses (FCHNs) are at a higher risk of experiencing emotional exhaustion and feelings of low personal accomplishment. Higher levels of professional identity may decrease these negative feelings. Its measurement could produce positive effects for FCHNs and the quality of care they offer.AimThis study aims to evaluate the psychometric properties (validity and reliability) of the Nurses Professional Values Scale-Revised (NPVS-R) on FCHNs in Italy.Research designA cross-sectional research design was used.Participants and research contextA convenience sample of FCHNs was recruited in an out-of-hospital setting from Italy. A total of 202 nurses were eligible (mean age of 41.11 ± 10.55 years; 78.2% female).Ethical considerationsThe study was performed in accordance with the World Medical Association Declaration of Helsinki. Participants were asked for their consent and were guaranteed anonymity in the information collected. The study was approved by the internal review board of the university.ResultsConfirmatory Factor Analysis (CFA) supported a unidimensional factorial structure of the NPVS-R with an adequate fit to the data. Internal consistency reliability was also supported. The construct validity was further reinforced by the concurrent validity results showing a positive and significant correlation of professional identity with job satisfaction.ConclusionThe NPVS-R is a valid and reliable instrument to measure professional identity among FCHNs. It can be used in clinical practice to improve FCHNs’ psychological-emotional feelings and quality of care provided, in research to allow comprehensive understanding of professional identity, and in educational settings to monitor the professional identity levels of Family and Community Health Nursing students.